ANALISIS PENDAPATAN USAHATANI KELAPA SAWIT RAKYAT DI DESA SEI LAMA, KECAMATAN SIMPANG EMPAT, KABUPATEN ASAHAN - gultom, rosmeta (Fakultas Pertanian UST, 2023)
This study analyzes to find out the amount of income earned by farmers and to find out the magnitude of the production and income risks faced by smallholder oil palm farmers from 2019-2021 in Sei Lama Village, Simpang Empat District, Asahan Regency. This research was conducted in Sei Lama Village, Simpang Empat District, Asahan Regency. This research was carried out starting from surveys, collecting data in the field and preparing reports. The results showed that the average income earned by farmers who had a land area of >1 Ha was IDR 556,529,160/Rp/Ha/semester, while farmers with the lowest income were farmers who had a land area of 0.6-1 Ha of IDR 91,884,000 /Rp/Ha/semester. The productivity of smallholder oil palm is 1.67/ha/month and the results of multiple linear regression show that the variable (X1) land area, and variable (X4) the number of dependents has a significant effect on (Y) the income of labor fishermen in Sei Lama Village, Simpang Empat District, Asahan Regency